PIANO TRIO IN THE COMPOSERS’ CREATION OF THE REPUBLIC OF MOLDOVA: HISTORICAL AND THEORETICAL ASPECTS - PLEȘCAN, IRINA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2023)
The chamber-instrumental ensemble is one of the oldest types of instrumental ensembles in music art, having a rich history. It is vividly represented in the composers’ creative work of different epochs, national schools and styles, ranging from European baroque to modern music. Regarding the whole variety of instrumental compositions in chamber music, the piano chamber-instrumental ensemble occupies the first place, thus, one of the most popular genres of chamber-instrumental ensemble can be considered the piano trio genre. In the present article, the evolution of Moldovan chamber instrumental music in the context of the formation of the Moldovan school of composition is studied. Also is given a brief review of musicological, methodological and reference literature, to some extent affecting the investigating issues of musical art. The methodological basis of the present article was the works written by the Moldovan musicologists of the Soviet period (A. Abramovici, S. Lobel, L. Axionova, I. Miliutina, E. Cletinici, etc.), works that appeared during the last three decades (E. Mironenco, I.Ciobanu-Suhomlin, S.Ţircunova, N. Cozlova, A.Lapicus, Iu. Mahovici, N. Chiciuc), as well as the works of young scientists who study the performance aspects of the piano trio written by the Moldovan composers (N. Costicova, N. Djalilova).